A look at competency assessment from the didactic approach, in primary education - Gómez Molano, Nancy Milena (2021)
This text contains a quick look at the immersion of the term competences to education and evaluation by competences, within the school classroom from didactics, understood, as the resources with which the teacher makes use of his pedagogy, the series of technological tools and materials that favor learning from concrete manipulation.Hence, the projections are evaluated from the formative evaluation of the competences, which are acquired through the didactic application of activities that are triggering in the learner, a character of significant learning, demonstrated in the process of solving problems raised and that are solved with the help of the teacher. This complex process achieves in the learner the being, knowing and knowing how to do in a given context, challenge to achieve that conglomerate of cultural diversity that are the students, acquire a quality education for life.